P145 INACTIVATION OF IRF1 CAUSES SUSCEPTIBILITY TO COLITIS-ASSOCIATED COLORECTAL CANCER. (7th February 2019) - Jeyakumar, Thiviya; Fodil, Nassima; Van Der Kraak, Lauren; Meunier, Charles; Cayrol, Romain; McGregor, Kevin; Langlais, David; Greenwood, Celia; Beauchemin, Nicole; Gros, Philippe
Abstract: Colorectal cancer is a highly prevalent malignancy worldwide, with an increased incidence in patients diagnosed with inflammatory bowel disorders (IBD). Risk of IBD is strongly influenced by genetic factors, including the IBD5 locus (5q31), harboring the IRF1 gene. Our studies have shown that in the azoxymethane (AOM)/dextran sodium sulfate (DSS) murine model of colitis-associated colorectal cancer (CA-CRC), loss of interferon regulatory factor 1 ( Irf1 ) results in enhanced tumorigenesis. Transcriptome profiling of AOM/DSS treated colons conducted early in the pathogenesis of CA-CRC showed heightened colonic inflammation and leukocyte infiltration in Irf1 -/ - mice compared to WT controls, well before the appearance of tumors. Immunoprofiling by flow cytometry revealed this to be a predominantly myeloid influx with an accumulation of proinflammatory Gr1+ Cd11b+ cells in the colons of mutant mice, as well as increases in CD3+ lymphoid cells and mast cell activation. Furthermore, CA-CRC experimentation in bone marrow chimeras proved that it was loss of Irf1 in the hematopoietic compartments that drove tumorigenesis. Finally, human correlative studies showed extensive overlap between genes upregulated in active ulcerative colitis lesions and AOM/DSS treated Irf1 -/ - mice, as well as decreased expression of IRF1 in later stage colorectal cancer, associated with poorer prognosis in these patients, establishing loss of IRF1 expression as a strong genetic signature to identify susceptible populations. The results from this study establish IRF1 as a major regulator of inflammatory response in situ in the gut, and as a major driver of colitis-associated colorectal cancer in both mice and humans.